Neprosin, a Selective Prolyl Endoprotease for Bottom-up Proteomics and Histone Mapping - Schräder, Christoph U; Lee, Linda; Rey, Martial; Sarpe, Vladimir; Man, Petr; Sharma, Seema; Zabrouskov, Vlad; Larsen, Brett; Schriemer, David C (Molecular & cellular proteomics, 2017)
Trypsin dominates bottom-up proteomics, but there are reasons to consider alternative enzymes. Improving sequence coverage, exposing proteomic "dark matter," and clustering post-translational modifications in different ways and with higher-order drive the pursuit of reagents complementary to trypsin. Additionally, enzymes that are easy to use and generate larger peptides that capitalize upon newer fragmentation technologies should have a place in proteomics. We expressed and characterized recombinant neprosin, a novel prolyl endoprotease of the DUF239 family, which preferentially cleaves C-terminal to proline residues under highly acidic conditions. Cleavage also occurs C-terminal to alanine with some frequency, but with an intriguingly high "skipping rate." Digestion proceeds to a stable end point, resulting in an average peptide mass of 2521 units and a higher dependence upon electron-transfer dissociation for peptide-spectrum matches. In contrast to most proline-cleaving enzymes, neprosin effectively degrades proteins of any size. For 1251 HeLa cell proteins identified in common using trypsin, Lys-C, and neprosin, almost 50% of the neprosin sequence contribution is unique. The high average peptide mass coupled with cleavage at residues not usually modified provide new opportunities for profiling clusters of post-translational modifications. We show that neprosin is a useful reagent for reading epigenetic marks on histones. It generates peptide 1-38 of histone H3 and peptide 1-32 of histone H4 in a single digest, permitting the analysis of co-occurring post-translational modifications in these important N-terminal tails.
Keywords: HeLa Cells; histony; Humans; Histones; HeLa buňky; Peptides; posttranslační úpravy proteinů; Recombinant Proteins; Proteomics; lidé; proteomika; Peptide Hydrolases; peptidy; proteasy; Protein Processing, Post-Translational; rekombinantní proteiny